Nobili padri. La generazione dell’Ottanta e la musica per film del secondo dopoguerra (Schermi. Storie e culture del cinema e dei media in Italia, 2020)
Many key film composers of the second half of the 20th century – including Giovanni Fusco and Nino Rota, the “voices” of Antonioni and Fellini’s cinemas – studied composition at the Roman Musical Academy of Santa Cecilia, under Alfredo Casella. The father of the “Generation of the Eighties” – the nickname coined by Massimo Mila to indicate the protagonists of Italian music born at the end of the 19th century – while not directly involved in the world of cinema, nonetheless looked curiously toward the possibilities that this new universe created for music and young composers. Rota and Fusco, but also other composers from Casella’s school like Goffredo Petrassi, played a leading role in the history of film music in the 20th century. Was this mere chance, or can it be indirectly connected to the teachings of the Turinese composer? This essay illustrates how Casella’s musical language and teachings, alongside the others of the Generation of the Eighties served as a point of reference for many film composers from the fifties. This was, the article argues, an organic adoption of musical codes and genres that the Generation passed on to its students, something made possible by the artisanal dimension that was common in film compositions at that time.